Study on Adsorption of Methylene Blue from Aqueous Solution by Biochar Derived from Mimosa Pigra Plant - Xuan Cuong, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 37 No 2DO - 10.25073/2588-1094/vnuees.4582, 2021)
Biochar from mimosa pigra was studied to remove methylene blue (MB) from aqueous solution. The properties of biochars were determined using Fourier Transform Infrared, scanning electron microscope, and Brunauer–Emmett–Teller. The biochar achieved the yield of 24.62 % at 500 o C pyrolysis. The specific surface area of ​​the biochar is 285.53 m 2 /g, the total pore size is 0.153 cm 3 /g and the ash content is 2.79%. The optimal dose of removing MB of the biochar is 5 g/L and the optimal pH is 2 - 10. MB removal reached over 80% in the first 30 min, followed by a stable period of 120 to 360 min reaching over 90% of removal. Maximum adsorption capacity reached 20.18 mg/g at 25 o C. MB adsorption data is suitable for kinetic models in order: Avrami > Elovich > PSO > PFO. The adsorption process may comprise physical and chemical adsorption andmultiple stages.